Inferring implications of climate change in south Florida hardwood hammocks through analysis of metacommunity structure. Issue 7 (8th April 2016) - Ross, Michael S.; Sah, Jay P.; Ruiz, Pablo L.; Spitzig, Adam A.; Subedi, Suresh C.
Abstract: Aim: In order to explore how variation in regional biogeography would affect forest responses to climate change, we analysed metacommunity structure of trees in natural forest fragments across a boundary between tropical and sub‐tropical temperature regimes. We wished to determine whether species assemblages were constrained by periodic cold temperatures, dispersal limitation and/or local processes associated with fragment size, and consider how these influences might affect future species migration and community reassembly. Location: Southeastern Florida, USA. Methods: We collected complete tree species lists for 144 forest fragments, from our own surveys supplemented by publicly available sources. The resulting species‐by‐site data matrix was re‐ordered based on an ordination that identified the latent environmental axis most responsible for variation in composition, and metacommunity structure was analysed for coherence, turnover and range boundary clumping. Matrix structure was tested for associations with site variables, and with community‐aggregated functional traits related to cold tolerance, dispersal limitation and fragment size. Results: Forest patch size was the strongest single correlate with composition and species richness, but mean January temperature and a neighbourhood index denoting degree of isolation from other patches contributed significantly to regression models. The species‐by‐site matrix was highly nested, with trees common to small upland fragments in the Everglades interior representing a distinct subset of the richer assemblages found in sites closer to the coast. Interior forests were smaller, more isolated, and subject to cooler minimum temperatures than more coastal forests, and were comprised primarily of early‐successional, animal dispersed species. Main conclusions: While warming winter temperatures may relax some constraints on the northward migration of tropical species through the region, sea level rise will raise ground water levels, decreasing the size and number of suitable mesic patches, and increasing their isolation. The result will be a loss in tree species diversity, especially among late‐successional, edge‐sensitive species.